Pembuatan Karbon Aktif dari Ampas Kopi Robusta dan Tempurung Kelapa dengan Variasi Konsentrasi Aktivator Kalium Hidroksida - Pusphaningrum, Saputri Anggraeni; Pramita, Ayu; Satriawan, Dodi (JURNAL INTEGRASI, 2023)
Coffee is a well-known and popular drink in Indonesia, because many young and old people like coffee and even make it a hobby. So that coffee shops in Indonesia have increased in recent years. The coffee shop certainly produces quite a lot of waste in the form of coffee grounds. Stacked coffee grounds can have a negative impact on health and the environment because coffee grounds contain harmful chemicals such as polyphenols, tannins and alkaloids. This study aims to utilize robusta coffee grounds and coconut shell waste as adsorbents in the form of activated carbon activated with potassium hydroxide (KOH) with varying concentrations of 5 and 10%. The best results in this study were robusta coffee grounds activated carbon activated with 10% KOH with a moisture content of 0.485%, ash content of 2.945%, volatile matter content of 97.52%, and absorption capacity of iodine 1,256.31 mg/g. and coconut shell activated carbon activated with 10% KOH with a moisture content of 0.725%, ash content of 0.51%, volatile matter content of 96.86%, and absorption of iodine 1,237.275 mg/g.